2018
DOI: 10.1002/bmc.4455
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring residue levels and dietary risk assessment of pymetrozine for Chinese consumption of cauliflower

Abstract: The present study investigates the occurrence of pymetrozine residues in cauliflower samples obtained from six cauliflower‐producing areas of China during fixed time periods in 2017 and estimates the dietary risk of pymetrozine in cauliflower. A liquid chromatography with tandem mass spectrometry method was developed and validated to detect pymetrozine in cauliflower. The samples were extracted using 20 mL of acetonitrile and purified with dispersive solid‐phase extraction using C18 as sorbent. The limit of qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
0
15
1
Order By: Relevance
“…After exposure to UV-light, the HI values obtained for the DM and λ-CHT ( Table 6 ) were greater than 1 which indicated a safe level of pesticide residues present in the cauliflower and these findings are in close agreement with those reported by Akomea-Frempong, et al [ 25 ]. In a similar study, it is demonstrated that the daily intake of cauliflower and many other brassica vegetables is 275 g per person in the Chinese population, which is used as the largest portion of cauliflower for the Chinese adults [ 54 ]. The residue behaviour, parent pesticide hazards, and distribution in environment and crops are well acknowledged environmental and food safety issues and have raised concerns on a large scale.…”
Section: Resultsmentioning
confidence: 99%
“…After exposure to UV-light, the HI values obtained for the DM and λ-CHT ( Table 6 ) were greater than 1 which indicated a safe level of pesticide residues present in the cauliflower and these findings are in close agreement with those reported by Akomea-Frempong, et al [ 25 ]. In a similar study, it is demonstrated that the daily intake of cauliflower and many other brassica vegetables is 275 g per person in the Chinese population, which is used as the largest portion of cauliflower for the Chinese adults [ 54 ]. The residue behaviour, parent pesticide hazards, and distribution in environment and crops are well acknowledged environmental and food safety issues and have raised concerns on a large scale.…”
Section: Resultsmentioning
confidence: 99%
“…Pymetrozine has only recently replaced organophosphate insecticides, thus there are very few studies regarding the exposure of operators and the community. Ingestion of vegetables and fruits is considered as the main exposure route of Pymetrozine in previous studies conducted in China (Jia et al, 2019, Gong et al, 2019, Kovacova et al, 2013, Yu et al, 2020. However, there is little study focus on the Pymetrozine exposure from soil and paddy water and its environmental health risk assessment for the agriculture communities in China.…”
Section: Exposure Assessment Through Environmental Mediamentioning
confidence: 99%
“…Pymetrozine {4, 5-dihydro-6-methyl-4-[(3-pyridylmethylene)-amino]-1, 2, 4-triazine-3(2H)-one}which has the basic structure of a pyridine azomethine (Zhang et al, 2015). Currently, is widely used in China (Jia et al, 2019, Gong et al, 2019, Kovacova et al, 2013. In addition, Pymetrozine has recently replaced organic phosphate pesticides although organophosphate pesticides continue to be used in some other countries in the world (Hamsan et al, 2017,Atabila et al, 2018, Phung et al, 2012a.…”
Section: Introductionmentioning
confidence: 99%
“…Apple and cabbage were purchased from a local supermarket in Guiyang, which were selected as representative food samples to confirm the feasibility of SERS method for detecting pymetrozine in food samples. All of these samples were tested to confirm the absence of pymetrozine by LC-MS/MS method [10,11]. The spiked apple and cabbage samples with adding levels of 0.2, 2.0, and 10.0 mg/kg were prepared by adding the pymetrozine working solution (the concentrations were 1.0, 10.0, and 100.0 mg/L, respectively) to these two homogenized samples.…”
Section: Sample Preparationmentioning
confidence: 99%
“…These results suggest that the expected residual concentration of pymetrozine in agricultural and food samples is rather low, thus it is necessary to establish rapid, sensitive, and economical methods for determination of pymetrozine residues. Up to now, many methods have been published for detection of pymetrozine residues, including gas chromatography [4], gas chromatography-tandem mass spectrometry (GC-MS), high-performance liquid chromatography (HPLC) [9], liquid chromatography-tandem mass spectrometry (LC-MS/MS) [10,11], colorimetry [12], electrochemical method [13] and differential pulse polarography [14]. Although these methods exhibit good sensitivity, nevertheless, there are some drawbacks in their applications, such as laborious, complex procedures, and dependent on expensive equipment.…”
Section: Introductionmentioning
confidence: 99%